Prevalence Rates and Risk Factors for Primary Open Angle Glaucoma in the Middle East - Rana Torabi; Alon Harris; Brent Siesky; Ryan Zukerman; Francesco Oddone; Sunu Mathew; Ingrida Januleviciene; Alice C. Verticchio Vercellin (Journal of Ophthalmic & Vision Research, 2021)
Abstract Glaucoma is a multifactorial disease and a leading cause of irreversible blindness worldwide. Current data has demonstrated the approximate distribution of primary open-angle glaucoma (POAG) in patients of European, African, Hispanic, and Eastern Asian descent. However, a significant gap in the literature exists regarding the prevalence of POAG in Middle Eastern (ME) populations. Current studies estimate ME POAG prevalence based on a European model. Herein we screened 65 total publications on ME prevalence of POAG and specific risk factors using keywords: “glaucoma”, “prevalence”, “incidence”, “risk factor”, “Middle East”, “Mideast”, “Persian”, “Far East”, as well as searching by individual ME countries through PubMed, Embase, Ovid, Scopus, and Trip searches with additional reference list searches from relevant articles published up to and including March 1, 2021. Fifty qualifying records were included after 15 studies identified with low statistical power, confounding co-morbid ophthalmic diseases, and funding bias were excluded. Studies of ME glaucoma risk factors that identify chromosomes, familial trend, age/gender, socioeconomic status, lifestyle, intraocular pressure, vascular influences, optic disc hemorrhage, cup-to-disc ratio, blood pressure, obstructive sleep apnea, and diabetes mellitus were included in this systematic review. We conclude that the prevalence of POAG in the ME is likely higher than the prevalence rate that European models suggest, with ME specific risk factors likely playing a role. However, these findings are severely limited by the paucity of population-level data in the ME. Well-designed, longitudinal population-based studies with rigorous inclusion and exclusion criteria are ultimately needed to accurately assess the epidemiology and specific mechanistic risk factors of glaucoma in ME populations.